2020
DOI: 10.1136/ijgc-2020-001879
|View full text |Cite
|
Sign up to set email alerts
|

Role of predictive markers for severe postoperative complications in gynecological cancer surgery: a prospective study (RISC-Gyn Trial)

Abstract: BackgroundSurgery for gynecological cancer involves highly invasive and complex procedures potentially associated with various complications, which can cause extended hospital stays and delay of subsequent therapy, with a detrimental effect on the prognosis. The aim of this study was to explore and define the predictors of severe postoperative complications in patients undergoing surgery for gynecologic cancer.MethodsPatients undergoing surgery for gynecologic cancers were analyzed prospectively from October 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Candidate predictors identified from previous research in patients with ovarian cancer were: age, BMI, polypharmacy, ASA classification, comorbidity, functional impairment, and FIGO stage. [23][24][25][26] Other predictors we hypothesized that could be relevant were: preoperative living situation, fall risk, pre-existing memory problems, history of confusion during illness, malnutrition, use of a walking aid, tumor grade and bowel surgery performed (as indicator of surgical complexity).…”
Section: Discussionmentioning
confidence: 99%
“…Candidate predictors identified from previous research in patients with ovarian cancer were: age, BMI, polypharmacy, ASA classification, comorbidity, functional impairment, and FIGO stage. [23][24][25][26] Other predictors we hypothesized that could be relevant were: preoperative living situation, fall risk, pre-existing memory problems, history of confusion during illness, malnutrition, use of a walking aid, tumor grade and bowel surgery performed (as indicator of surgical complexity).…”
Section: Discussionmentioning
confidence: 99%
“…In our previous publications, we demonstrated that restrictions in QoL domains such as physical functioning had a significant effect on the risk of severe postoperative complications [ 11 , 12 ]. Furthermore, we found that patients with debilitating symptoms and cognitive impairment had an increased risk of developing severe postoperative complications [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…This work is a subgroup analysis of the data from a prospective study ”Role of Predictive Markers for Severe Postoperative Complications in Gynecological Cancer Surgery” (RISC-GYN Trial) [ 12 ]. The study was designed to identify predictors for severe postoperative complications in patients with gynecological cancer.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations